Ingredients of a Natural Oral Nutritional Supplement and Their Role in the Treatment of Osteoarthritis. Issue 15 (March 2022) - Bharat, Krish Tejas; Manhas, Navdeep Singh; Gutcho, James; Lin, Joshua; Bhattacharyya, Sumon; Kounang, Robertus
Osteoarthritis is a prevalent degenerative disease affecting a large portion of the world's aging population. Currently, nonsteroidal anti-inflammatory drugs and acetaminophen are first-line medications for treating osteoarthritis patients' pain. However, several studies have noted that while these medications control pain they do not halt progressive degeneration and tend to have an unfavorable side-effect profile with prolonged use. Recently, due to their more favorable side-effect profiles, herbal alternatives for controlling osteoarthritis symptoms and for alleviating the progression of the disease are being increasingly studied. Synogesic is a newly developed herbal supplement blend by renowned orthopedic surgeons and physiatrists consisting of turmeric, rutin, ginger root, vitamin C, vitamin D, and boswellia extracts. A study by Sharkey et al. has commented on the efficacy of the blend on the patients with knee osteoarthritis. So far, a review on the ingredients of the blend has not yet carried outbeen. By exploring prominent literature databases including PubMed and ScienceDirect, our aim is to write a narrative review to explore the individual ingredients of this blend and delve into their characteristics, as well as the most recent literature on their mechanism and efficacy in patients with osteoarthritis. Through this, we hope to inform clinicians and patients alike on relevant up-to-date research on the supplement and provide insight on the potential for this supplement for alleviating the disease course of patients with osteoarthritis.